Development of Dance Movements with Local Wisdom to Increase Tolerance Attitude - Siti Alsyamsari Abriyanti; Elindra Yetti; Romi Nursyam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Tolerance is one of the core character values that is crucial to instill from an early age, especially in multicultural societies like Indonesia. However, early childhood education (ECE) still tends to focus on cognitive and motoric aspects, while the integration of social values such as tolerance has not yet received adequate attention in the curriculum. This study aims to explore the potential of local wisdom-infused dance movements as an educational medium for instilling tolerance values in young children. The research employs a systematic literature review approach, analyzing previous studies relevant to three main variables: dance movements, local wisdom, and tolerance values in early childhood. The findings reveal that dance movements are not only beneficial for physical and aesthetic development but also serve as an effective expressive medium for fostering empathy, cooperation, and acceptance of differences. Integrating local wisdom values into dance activities can strengthen children's cultural identity and cultivate awareness of cultural diversity from an early age. Furthermore, emotional engagement and hands-on experiences in artistic activities have proven more effective in character building compared to conventional approaches. This study offers theoretical and practical contributions by formulating a local dance-based learning model explicitly aimed at reinforcing tolerance attitudes. The implications of these findings provide new directions for developing more contextual and culturally rooted ECE curricula, as well as enriching character education strategies that are engaging and meaningful for children. Thus, dance movements serve as a vital bridge in nurturing an inclusive, open-minded, and diversity-ready young generation.